ANALISIS KESESUAIAN MUTU PINDANG IKAN LAYANG (Decapterus sp.) TERHADAP STANDAR NASIONAL INDONESIA - Wardani, Maulidiya; Ramli, Ramli; Jamil, Siti Nur Aisyah (Universitas Islam Madura, 2024)
The strategy to ensure that preserved fish buying and selling transactions at the preserved fish marketing center in Kulon City, Bondowoso Regency can continue is to ensure that the quality of the preserved fish traded at the preserved fish marketing center complies with the quality standards set by the government, namely the Indonesian National Standard (SNI). The aim of this research is to determine the conformity of the quality of the preserved flying fish with the Indonesian National Standards (SNI). This research method begins with sampling preserved flying fish at the Preserved Fish Marketing Center, Kulon City, Bondowoso Regency and then taken to the UPT Laboratory for Quality Testing and Development of Marine and Fishery Products Banyuwangi for sample testing. Testing of samples of preserved flying fish products according to the requirements of SNI 2717:2017, namely organoleptic tests, microbiological tests and chemical tests. Organoleptic test (SNI. 2346:2015) which includes appearance, smell, taste and consistency. Microbiological tests consist of aerobic TPC (SNI. 2332.3:2015), Escherichia coli (SNI. 2332.1:2015), Salmonella (SNI. 2332.2:2006) and Staphylococcus aereus (SNI. 2332.9:2015). Chemical tests consist of water content (SNI. 2354.2:2015), salt content (SNI. 01-2359-1991), histamine (SNI. 2354.10:2016) and lead (Pb) (IKM 3.14 (ICP-MS). The results of the research showed that the results of testing the quality of the preserved flying fish consisted of organoleptic tests (appearance, smell, taste and consistency), microbiological tests (aerobic TPC, Escherichia coli, salmonella, and Staphyloccocus aureus), and chemical tests (moisture content, salt content , histamine and lead), shows that the quality of preserved flying fish at the preserved fish marketing center in Kulon City, Bondowoso Regency is in accordance with the Indonesian National Standard, namely SNI 2717:2017 Keyword: preserved flying fish, quality conformity, SNI